Outdoor Leadership Competencies A Research Study Surveying Outdoor Leaders - Swiderski, Michael J. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
The study identified land-based outdoor leadership competencies deemed necessary by outdoor leaders in the western United States. Using resources such as outdoor leadership literature, competency-based teacher education manuals, consultation with outdoor leadership specialists in educational, private, and governmental agencies, and personal outdoor leadership experience, a list of 50 outdoor leadership competencies was developed. The list was sent to 282 outdoor leaders, administrators, and educators who ranked the importance of each competency. The return rate was 52.5% (148). Six weeks after the initial mailing, data were analyzed using a six-point Likert-type scale. Competencies were prioritized and ranked in order of importance using the statistical mean for each competency statement. Thirty-four competencies were ranked "extremely important." Among these were: exercise good judgment and common sense while performing duties as a leader under stress and pressure; handle situations which pose potential safety problems; foresee and be prepared for situations in which problems and accidents might occur; and prevent illness or injury but if either occurs, recognize and apply proper procedures and controls to stabilize or improve the ill or injured person's condition. Of the last 16 competencies, 14 were ranked "of moderate importance" and 2 were ranked "not important." (NQA)
ERIC Note: Paper presented at the American Camping Association Convention (San Diego, CA, February 27-March 3, 1984).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Job Skills; Leadership; Leadership Qualities; Minimum Competencies; Outdoor Education; Outdoor Leadership; Safety; Skill Analysis; United States (West); Reports, Research; Speeches/Meeting Papers